Water quality model with multiform of N/P transport and transformation in the Yangtze River Estuary - 王彪 卢士强 林卫青 杨漪帆 王道增 (Journal of hydrodynamics. Series B, 2016)
As the Yangtze River Estuary and adjacent sea have been classified as a problem area with regard to eutrophication, it is important to explore the spatial and temporal variations of nitrogen and phosphorus （N/P） nutrients in this area. Based on danish hydraulic institute （DHI）＇s open platform Ecolab, a hydrodynamic and water quality model was developed for the Yangtze River Estuary, in which the transport and transformation processes of different forms of N/P nutrients were considered. Validations against measured data show that the model is overall reliable. Preliminary application of the model suggests that the model can simulate the characteristics of high phosphorus concentration area in the Yangtze River Estuary, and the high concentration area is closely related to the resuspension process of particulate phosphorus.